Grain size effects in donor doped lead zirconate titanate ceramics - Picht, Gunnar; Khansur, Neamul Hayet; Webber, Kyle Grant; Kungl, Hans; Hoffmann, Michael J.; Hinterstein, Manuel (Journal of Applied Physics, 2020)
The ferroelectric, ferroelastic, and dielectric properties as well as the crystal structure were investigated for polycrystalline donor doped lead zirconate titanate (PZT) with grain sizes ranging from 0.25 to 5 μm, which were prepared using a novel zirconium titanium hydrate precursor (ZTH) with a specific surface area of 310 m2/g. Piezoforce microscopy was used to investigate the change in the domain structure, revealing a change in the domain configuration from a complex 3D structure to a simple lamellar domain formation at a 1 μm grain size that corresponded to a rapidly increasing internal mechanical stress observed with in situ synchrotron x-ray experiments. The correlation between the change in domain configuration, increasing internal stresses, effects of poling on the crystal structure, and the macroscopic ferroelectric and ferroelastic properties are discussed in detail, allowing a deeper understanding of size effects in polycrystalline donor doped PZT ceramics.
CRIS-Team Scopus Importer:2020-12-25